2022
DOI: 10.1111/ijfs.15600
|View full text |Cite
|
Sign up to set email alerts
|

First accurate profiling of antioxidant anthocyanins and flavonols of Tibouchina urvilleana and Tibouchina mollis edible flowers aided by fractionation with Amberlite XAD‐7

Abstract: Summary A purification and fractionation process of the edible flowers of Tibouchina mollis and Tibouchina urvilleana followed by the first attempt to the anthocyanin and flavonol characterisation and identification by UHPLC‐DAD‐ESI‐MS were developed. T. urvilleana exhibited a higher monomeric anthocyanin content, mainly due to the presence of the 3‐O‐(6′‐p‐coumaroyl)‐glucoside derivatives of malvidin and petunidin. Quercetin‐3‐O‐hexoside was the major flavonol identified in T. urvilleana, and the lack of myri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Ramírez‐Bolanos et al (2021) reported that dried banana flower and dried banana pseudostem may have the potential to be used as food ingredients due to the phenolic profile of dried banana flower and its byproducts. Solarte et al (2022) determined that a deficiency of myricetin derivatives was also detected in Tibouchina urvilleana . The anthocyanin and flavonol profile of Tibouchina mollis was more diverse, with the formation of cyanidin‐3‐O‐glucoside followed by 3‐O‐(6′‐p‐coumaroyl)‐glucoside and 3‐O‐glucoside derivatives of malvidin and petunidin as anthocyanins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramírez‐Bolanos et al (2021) reported that dried banana flower and dried banana pseudostem may have the potential to be used as food ingredients due to the phenolic profile of dried banana flower and its byproducts. Solarte et al (2022) determined that a deficiency of myricetin derivatives was also detected in Tibouchina urvilleana . The anthocyanin and flavonol profile of Tibouchina mollis was more diverse, with the formation of cyanidin‐3‐O‐glucoside followed by 3‐O‐(6′‐p‐coumaroyl)‐glucoside and 3‐O‐glucoside derivatives of malvidin and petunidin as anthocyanins.…”
Section: Resultsmentioning
confidence: 99%
“…The anthocyanin and flavonol profile of Tibouchina mollis was more diverse, with the formation of cyanidin‐3‐O‐glucoside followed by 3‐O‐(6′‐p‐coumaroyl)‐glucoside and 3‐O‐glucoside derivatives of malvidin and petunidin as anthocyanins. As flavonol compounds, myricetin, quercetin and kaemperol, and quercetin 3‐O‐hexosides were characterized (Solarte et al, 2022). Grajeda‐Iglesias et al (2022) reported that the first lypophilization of ellagitannins from pomegranate peel was carried out, and based on previous studies, polyphenols (an anthocyanin and a phenolic acid) extracted from hibiscus flowers were successfully lypophilized.…”
Section: Resultsmentioning
confidence: 99%
“…Betalains were eluted from the column with three volumes of water type II (PE2), and then the betalain extract (PE2) was lyophilized (Figure 7). The colorless polyphenols, together with sugars and organic acids, from PE1 that were retained in the resin were eluted with methanol/acid (19:1) to be discarded [34].…”
Section: Separation Of Polyphenols With Ambertite Xad-7 From Pe1mentioning
confidence: 99%
“…Subsequently, 30 µL of betaxanthin was added to 3 mL of the diluted solution of ABTS •+ . After stirring for 1 min and waiting for 6 min, the absorbance at 734 nm was spectrophotometrically measured (UV-Vis Pharo, Merck, Darmstadt, Germany) [34,36]. Results were obtained by interpolation of the absorbance in the trolox calibration curve (0.5-2.5 µM).…”
Section: Determination Of Antioxidant Capacity Equivalent To Trolox (...mentioning
confidence: 99%